Desenvolvimento, avaliação sensorial e da composição nutricional de preparações destinadas a esportistas - Sabrina Alves Ramos; Bárbara Ferreira dos Santos; Francine Rafaela Fernandes da Silva; Lívia Muniz Cirino de Carvalho; Janaína Lavalli Goston (Universidade do Estado do Rio de Janeiro, 2020)
Introduction: The association of balanced diets with physical exercise is increasing due to the population's current concern with physical well-being and a healthy lifestyle. However, food preparations that offer good nutritional value along with attractive sensory characteristics are not found often by the public. Objective: The objective of this study is to develop four food preparations (protein bar, date candy, sweet potato pie, and caprese pate) for sportspersons and to verify the nutritional profile, acceptability, and consumption intention of each food preparation. Methods: Sensory and consumption intention evaluation were performed with 224 tasters using a hedonic scale of 9 points. Ingredients with reduced levels of sugars, sodium, and saturated fats were prioritized for the development of the food preparations. Results: In the consumption intention and sensory evaluation tests, for all attributes evaluated, the food preparations protein bar, date candy, sweet potato pie, and caprese pate presented average scores higher than 6, and an acceptability index higher than 75%. Regarding the nutritional value, the protein bar and sweet potato pie presented good protein, energy, and carbohydrate content, and the date candy and the caprese pate stood out for the low number of calories, and total and saturated fats. Conclusion: It is concluded that the results found are satisfactory, given that a large number of consumers, amid a harsh daily routine, are in search of food preparations that can combine flavor, practicality, and cost-benefit, that will ultimately result in health and physical well-being.